2000
DOI: 10.1046/j.1526-4610.2000.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Correlates and Impact of Chronic Tension‐type Headaches

Abstract: Chronic tension-type headache has a greater impact on individuals' lives than has generally been realized, with affective distress being an important correlate of impairment. If treatment is to remedy impairment in functioning, affective distress, as well as pain, thus needs to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
168
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(178 citation statements)
references
References 31 publications
8
168
0
1
Order By: Relevance
“…Thus, catastrophizing may mediate the relationship among all three conditions and lead to increasing physical and mental symptoms. As a result, a persons' perception of pain may be amplified in the context of depression and anxiety 25,26 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, catastrophizing may mediate the relationship among all three conditions and lead to increasing physical and mental symptoms. As a result, a persons' perception of pain may be amplified in the context of depression and anxiety 25,26 .…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the evidence is fairly consistent that tension headache patients are more likely than healthy controls to suffer from psychiatric disorders, especially anxiety and depression. [28][29][30][31] Psychiatric disorders that may accompany migraine or tension-type headaches (especially depression) might cause dysfunction in the sexual response cycle. Maizels et al 23 have reported that the prevalence of sexual dysfunction does not differ in the presence of depression or anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…If one of the reasons for treatment is to decrease functional impairments, then depression as well as headache pain needs to be addressed. 7 Physicians also need to remember the high prevalence of depression in patients with headache when considering medications used to treat recurrent headaches. Several of the medications that might be considered, such as ␤-blockers, antianxiety agents, and narcotics, may possibly worsen depression.…”
Section: Discussionmentioning
confidence: 99%
“…Because the symptoms of depression are often subtle and hard to verbalize, these symptoms may be overlooked in patients who present with headache as their chief complaint. 7,8 Several instruments have been used in the primary care setting to screen for depression among adults. The most commonly used measures in outpatient settings are the Beck Depression Inventory; the Center for Epidemiologic Studies Depression Scale, Revised; the PRIME-MD Patient Health Questionnaire (PHQ-9); and the Zung Self-Rating Depression Scale.…”
Section: Reported In 2000mentioning
confidence: 99%